Evaluation of growth performance traits of F1 progenies derived from crossbred of an exotic chicken with Nigerian Indigenous chicken - David, Ifanegan Oluwadamilare; Oladejo, Ojedapo Lamidi; Margaret, Adedibu Tolulope; Olabayonle, Fasasi Abdulhakeem; Deborah, Popoola Abimbola; Abiola, Oyetoro Blessing; Olajumoke, Abdulrauf Bilqees (Brazilian Journal of Science, 2024)
Data were obtained for growth traits from fifty (50) progenies from straight crossing produced from crosses involving Arbor Acre (broiler) cocks and Nigerian Indigenous (Normal feather and naked neck) hens. Significant differences (p < 0.05) were observed in breed and sex across all bodyweight and body linear measurements at 4-12 weeks of age. The result indicated that Arbor acre naked neck (AANN) birds had the highest body weight (120.95 g), keel length (5.11 g), and shank length (7.34 g). Also, AANN had the highest feed intake (148.40 g) with AANN having a good FCR of 3.98 and WG of 37.33. There were also similar body weights of AANN (456.20 g) and AANF (302.73 g) at 8 weeks of age, while the feed conversion rate was also observed to be better in AANN (1.61) than Arbor acre normal feather (1.70). The interaction effects of growth traits revealed slightly similar values for both sexes in AANF while male AANN outperformed across all parameters measured except for keel length It was concluded that Arbor Acre x Naked neck (AANN) had higher morphometric characteristics and also exhibited higher values for growth performance than Arbor Acre x Normal feather (AANF), hence can be utilized for meat purposes if further study can be conducted on it.